2016
DOI: 10.1177/1073191116641181
|View full text |Cite
|
Sign up to set email alerts
|

Forced-Choice Assessment of Work-Related Maladaptive Personality Traits: Preliminary Evidence From an Application of Thurstonian Item Response Modeling

Abstract: This article describes an investigation of whether Thurstonian item response modeling is a viable method for assessment of maladaptive traits. Forced-choice responses from 420 working adults to a broad-range personality inventory assessing six maladaptive traits were considered. The Thurstonian item response model's fit to the forced-choice data was adequate, while the fit of a counterpart item response model to responses to the same items but arranged in a single-stimulus design was poor. Mono-trait hetero-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 92 publications
(125 reference statements)
3
68
0
Order By: Relevance
“…In these contexts, the MFC format might lead to more accurate inferences than the RS format. The MFC format has already been applied to a variety of constructs, including broad personality traits such as the Big Five (Brown & Maydeu-Olivares, 2011;Lee et al, 2018) and adaptive and maladaptive work-and performance-related dimensions (Brown & Maydeu-Olivares, 2013;Guenole et al, 2018;Stark et al, 2014;Stark, Chernyshenko, Drasgow, & White, 2012). This study compared an MFC and an RS version of a Big Five instrument, the Big Five Triplets, with respect to construct validity, criterion-related validity, and test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…In these contexts, the MFC format might lead to more accurate inferences than the RS format. The MFC format has already been applied to a variety of constructs, including broad personality traits such as the Big Five (Brown & Maydeu-Olivares, 2011;Lee et al, 2018) and adaptive and maladaptive work-and performance-related dimensions (Brown & Maydeu-Olivares, 2013;Guenole et al, 2018;Stark et al, 2014;Stark, Chernyshenko, Drasgow, & White, 2012). This study compared an MFC and an RS version of a Big Five instrument, the Big Five Triplets, with respect to construct validity, criterion-related validity, and test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, only a few studies have done this. Among those few studies, most have examined the equivalence of dominance-model-based SS and FC formats and found generally supportive evidence (Brown & Maydeu-Olivares, 2011Guenole, Brown, & Cooper, 2016;Lee, Lee, &Stark, 2018). However, as mentioned above, evidence has been accumulating that shows ideal point models more accurately capture the response processes underlying various psychological measures.…”
Section: Psychometric Equivalence Between Fc and Ssmentioning
confidence: 93%
“…If these assumptions do not hold empirically, treating FC estimates and SS estimates as equivalent may be problematic. For example, Guenole, Brown, and Cooper (2016) found that statement factor loadings differed substantially between FC and SS formats, suggesting that respondents may interpret them differently. Much more empirical data are needed to examine their degree of equivalence.…”
Section: Psychometric Equivalence Between Fc and Ssmentioning
confidence: 99%
“…Moreover, the PID-5 Over-reporting Scale [97] can detect the tendency to exaggerate or fabricate personality problems, and further scales are available for detecting different types of faking good [98]. A promising way to deal with such response patterns is using alternative measures that employ forced choice technique such as the Goldsmiths-60-item questionnaire [99]. [115][116][117][118][119][120][121][122][123].…”
Section: Further Issuesmentioning
confidence: 99%